Composition and Properties of Triple Superphosphate Obtained from Oyster Shells and Various Concentrations of Phosphoric Acid - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Nongnuch Laohavisuti; Kittichai Chaiseeda; Wimonmat Boonmee (My University, 2021)
Triple superphosphates [TSPs, Ca(H2PO4)2·H2O] were produced by exothermic reactions of oyster shells and different concentrations of phosphoric acid (10, 20, 30, 40, 50, 60, and 70% w/w) in a molar ratio of 1:2. The percentage yields, P2O5 and CaO contents, metal impurities, and thermal behaviors of all the as-prepared products are dependent on the concentrations of phosphoric acid added during the production processes, which confirm to get the best optimum of 60% w/w phosphoric acid. All the as-prepared products were characterized by several characterization methods [X-ray fluorescence, thermal gravimetric/derivative thermal gravimetric analysis, powder X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy], verifying that all the obtained compounds are TSP that can be used as fertilizers without metal toxic contaminants. From the successful results, the method for TSP production can be applied in the fertilizer industry based on starting waste materials of oyster shells that can replace the use of unsustainable phosphate or calcium minerals obtained from nonliving things.
Keywords: Phosphoric acid; Exothermic reaction; Gravimetric analysis; Seismic vibrator; Phosphorite; Phosphorus and nutrient management